Analisis Neraca Air Untuk Kebutuhan Air Irigasi di Daerah Aliran Sungai (DAS) Tukad Buleleng, Kabupaten Buleleng - ARFIANA, FIRDA; SUYARTO, R.; WIYANTI, WIYANTI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Analysis of Water Balance for Irrigation Water Needs in Tukad Buleleng  Watershed, Buleleng Regency Population and human activity have increased so that land use changes resulting in the catchment area does not function optimally. Poor watershed function conditions result in water in the dry season becoming scarce. Drought occurs due to upstream imbalance of watersheds that undergo land function, so the water needs for rice fields are not met. The purpose of this study is to analyze the needs of irrigation water. The method used is descriptive quantitative by calculating from the stage of crop water requirement/CWR, farm water requirement/FWR and project water requirement/PWR. The results showed that the highest value of water needs/PWR projects occurred in the planting period I November III during the generative phase of 196,90 liters/second and the lowest occurred in the planting period II in May I during the fertilization and ripening phase 156,40 liters/second.